EVALUATION OF LOW RESISTIVITY LOW CONTRAST RESERVOIR - Muhammad Amin Nizar Bin Che Abd Razak, Muhammad Amin (Universiti Teknologi Petronas, 2012)
The combination of conventional logs such as density, neutron and resistivity logs is proven to be very effective in the evaluation of normal reservoirs. An accurate determination of the petrophysical parameters with the conventional logs for low resistivity reservoirs is very difficult. The problem of these reservoirs is that conventional logging interpretation shows water zones, but water free hydrocarbon would be produced. In the case of low resistivity contrast reservoirs it is very hard to determine water hydrocarbon contact with resistivity logs. The project will involve on remodeling of low contrast reservoir by represent it by saturated core sample. The resistivity of the core sample saturated with different fluids will be compared to see any effect of low contrast reservoir. Nuclear Magnetic Resonance (NMR) logging method would be also suggested as an alternative to the conventional logging method since the method shown the capability to resolve the problem with low contrast reservoir without the needs of very thorough interpretation. The NMR logging method will make the process of evaluating the LRLC reservoir easier and more accurate.